Evolution of band structures in MoS2-based homo- and heterobilayers. (12th January 2016) - Zhu, H L; Zhou, C J; Huang, X J; Wang, X L; Xu, H Z; Lin, Yong; Yang, W H; Wu, Y P; Lin, W; Guo, F
Abstract: Density functional theory calculations have been performed to elucidate the detailed evolution of band structures in MoS2 -based homo- and heterobilayers. By constructing the energy-band alignments we observed that biaxial tensile and compressive strain in the constituent transition-metal dichalcogenide (TMD) monolayer shifts the states at the K C, Q C, and K V points down and up, respectively, while the states at the ΓV point are almost unaltered. In contrast, interlayer coupling tends to modify the states at the ΓV and Q C points by splitting the band-edge states of two strained or unstrained constituent TMD monolayers, while it does not affect the states at the K C and K V points. Considering the combined actions of strain and interlayer coupling, the relevant electronic parameters, especially the detailed evolution processes, of the band structures of the investigated bilayer systems can be clearly described. When further applying the extra biaxial strain to the three bilayer systems, it is found that energy differences Δ E ( K C − Q C ) and Δ E ( K V − ΓV ) decrease linearly as the increasing of the biaxial strain. According to the varying trends of Δ E ( K C − Q C ) and Δ E ( K V − ΓV ), MoS2 bilayer will maintain the indirect-bandgap character under any compressive or tensile strain. Differently, WS2 /MoS2 heterobilayer transforms interestingly to the direct-bandgap material under the strain from −1.6% to −1.2% with the valence band maximum and conduction band minimum located at the K C and K V point respectively. The direct-to-indirect bandgap transition can be obtained for the WSe2 /MoS2 heterobilayer when applying much larger extra tensile or compressive strain. The results offer an effective route to verify and tailor the electronic properties of TMD homo- and heterostructures and can be helpful in evaluating the performance of TMD-based electronic devices.